Perishable Produce Under Food Regulation - Gephart, W. F. (Quarterly Journal of Economics, 1918)
Stabilization of perishables aimed at; regulations to this end, 621. — Characteristics of the market for perishables, 623. — Fair prices determined at short intervals by agreement, 625. — Rejection of goods shipped, 628. — Salutary action of Food Administration, 629. — Methods of marketing, 631. — Conclusion, 634.